Diversity and community structure of insects on sugar palm and their correlation with abiotic factors in Tanah Datar Regency, West Sumatra Province, Indonesia - Zahlul Ikhsan; Sri Heriza; Siska Efendi; Arifda A.S. Waruwu; Sandy Miranda Pranata; Abdel Raheem (Treubia, 2026)
Sugar palm (Arenga pinnata Merr.) agroecosystems provide important ecological functions in tropical agricultural landscapes, particularly as habitats for pollinator insects and other arthropod communities. However, information regarding insect diversity and the influence of environmental factors on pollinator activity in sugar palm agroecosystems remains limited in Indonesia. This study aimed to evaluate insect diversity and community structure, and to examine the relationships between abiotic factors and insect abundance in sugar palm agroecosystems in Tanah Datar Regency, West Sumatra, Indonesia. Field observations were conducted in Lintau Buo and Sungayang Districts in 2025. Insects associated with sugar palm inflorescences were sampled during morning and afternoon observation periods using direct observation and sweep net methods. Community structure was analyzed using diversity, evenness, richness, and dominance indices. At the same time, the effects of abiotic variables on pollinator abundance were assessed using Negative Binomial Generalized Linear Models (GLM) and Spearman rank correlation analysis. A total of 2,297 insect individuals were recorded, consisting of 1,858 pollinator insects and 439 visitor insects belonging to 13 genera. Pollinator communities were dominated by Apis spp., Vespa sp., Polyrhachis spp., Episyrphus sp., and Tetragonula spp. Diversity analysis indicated moderate insect diversity, with high evenness and low dominance, suggesting relatively stable ecological conditions within the agroecosystem. Negative Binomial GLM revealed that rainfall significantly reduced pollinator abundance (Estimate = −0.084 ± 0.021 SE, p < 0.001), while relative humidity also negatively affected pollinator activity (p = 0.006). Spearman correlation analysis confirmed a strong negative relationship between rainfall and pollinator abundance (rs = −0.82, p < 0.01). These findings demonstrate that sugar palm agroecosystems support diverse insect communities and highlight the importance of environmental conditions in regulating pollinator activity within tropical agroforestry systems.